Domestic Violence Crimes: Legal Sanctions and Implication - Anwar, Mohamad; Shodiq, Md.; Darodjat, Tubagus Achmad (Journal Evidence Of Law, 2024)
This article discusses the application of criminal sanctions against perpetrators of domestic violence (KDRT) according to Law No. 23/2004 on the Elimination of Domestic Violence. Criminal sanctions are not only aimed at providing a deterrent effect to perpetrators but also as a form of legal protection for victims. This article also discusses the relevance of the concept of restorative justice as an alternative resolution in domestic violence cases to achieve balanced justice. The method used is descriptive-analytical with a normative approach, analyzing the application of law and the effectiveness of sanctions.